Analysis of Human Resource Management Policies and Their Impact on the Civil Service in Iraq (A field study in the Iraqi Health Administration) - Ali, Ali Saadoon (Journal of Economics and Administrative Sciences, 2020)
This research aims to analyze and the impact of human resource management policies (as an independent variable) contained in the public sector reform program on the civil service (as a dependent variable). The importance of the research lies in the implementation and implementation of various projects in the reform groups of the public sectors and the human resource management system in particular, By analyzing the administration’s trends and policies, identifying all strengths, working to improve and increasing its efficiency rates, working to identify, fix and remove all weaknesses, as well as working to replace them with strengths, and then work to develop resources in more than one form, especially human resources The research problem was also represented in finding the knowledge that the Iraqi state carries out in determining all the administrative foundations used in human resources and how to integrate them into the public health sector, in order to achieve and organize the social reform program that the state aims to achieve using the various civilized and widespread methods spread around the world to improve the field services provided For individuals without discrimination or racism, as it works to improve the role of human resources and take care of the main pillar present in it and expressed in it, through the evaluation and evaluation of the human element using the criteria of equality and equal opportunities, control and transparency, and to clarify the relationship between the research variables, the descriptive analytical approach was used in the study To renew the effects of human resources management and the policies used in the public sector, where the number of the sample used was 160 individuals as an experimental sample. One hundred (100) individuals were physicians, and sixty (60) nurses were in (7) hospitals, including governmental and some private, and the data were analyzed. In the statistical program (spss) and (Excel), using a number of statistical methods, including (arithmetic mean, mean deviation (Yari, Alpha Crow Nbach Factor, Pearson Correlation) The research has reached many results, the most important of which are identifying the different trends in each of them, the integrity and efficiency provided in identifying the different actors between different organizations and establishments, as well as the trends for human development resources and the development programs responsible for that.